EFEKTIFITAS PENGUKURAN CAPABILITY LEVEL TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN KERANGKA KERJA COBIT 2019 - aan erlansari; Ikhlasul Amal; andang wijanarko (JSAI (Journal Scientific and Applied Informatics), 2023)
The Office of Communication and Informatics, hereinafter referred to as Diskominfo, is a regional apparatus that carries out Regional Government affairs in the field of communication and informatics, the field of coding, and the field of statistics. Currently, the “X” Regency Communication and Informatics Office has implemented information technology governance as indicated by the SPBE implementation at the “X” Regency Regional Government, then has used electronic-based applications according to e-government classification, and the implementation of Standard Operating Procedures (SOP) related to policies applicable governance policies. However, there are several problems at the Diskominfo “X” Regency, namely problems regarding human resources, assets and supervision. Therefore it is necessary to measure the capability level of IT governance with the aim of knowing the level of capability and providing recommendations for IT governance using the 2019 COBIT framework. Based on the results of the 2019 COBIT assessment, the capability level of IT governance at Diskominfo, “X” Regency is at level 1 namely the Performed Process, which means that the implemented process has succeeded in achieving its goals. In order for IT governance at the Diskominfo “X” Regency to achieve the desired capability level, namely at level 3 (Established Process), the recommendations that need to be made are optimizing the existing human resources, involving the Diskominfo itself in managing human resources, making a priority list for installation and developing electronic-based applications, and establishing Standard Operational Procedures relating to performance targets and suitability.